Multiscale imaging reveals the presence of autophagic vacuoles in developing maize endosperm - Arcalís, Elsa; Hörmann-Dietrich, Ulrike; Stöger, Eva (Frontiers in Plant Science, 2023)
Cereal endosperm is solely devoted to the storage of proteins and starch that will be used by the embryo upon germination. The high degree of specialization of this tissue is reflected in its endomembrane system, in which ER derived protein bodies and protein storage vacuoles (PSVs) are of particular interest. In maize seeds, the main storage proteins are zeins, that form transport incompetent aggregates within the ER lumen and finally build protein bodies that bud from the ER. In contrast to the zeins, the maize globulins are not very abundant and the vacuolar storage compartment of maize endosperm is not fully described. Whereas in other cereals, including wheat and barley, the PSV serves as the main protein storage compartment, only small, globulin-containing PSVs have been identified in maize so far. We present here a multi-scale set of data, ranging from live-cell imaging to more sophisticated 3D electron microscopy techniques (SBF-SEM), that has allowed us to investigate in detail the vacuoles in maize endosperm cells, including a novel, autophagic vacuole that is present in early developmental stages.